Снежная девочка - Кастильо Хавьер (Tok. Мировой бестселлер, 2023)
Экземпляры: ЦБ\15\16\18\23 (20240918) / Инвентарный номер: 67071 / Цена: 458.00 / Сис.шифр: И(исп) / Авт.знак: К 28 / ГРНТИ: 17.82.31 / ББК: 84(4Исп)